Frontiers of Applied and Computational Mathematics : Proceedings of the 2008 Conference. - Blackmore, Denis L. (World Scientific, 2008)
This volume contains a selection of papers presented at the 2008 Conference on Frontiers of Applied and Computational Mathematics (FACM'08), held at the New Jersey Institute of Technology (NJIT), May 1921, 2008. The papers reflect the conference themes of mathematical biology, mathematical fluid dynamics, applied statistics and biostatistics, and waves and electromagnetics. Some of the world's most distinguished experts in the conference focus areas provide a unique and timely perspective on leading-edge research, research trends, and important open problems in several fields, making it a "mu.